The Effect of Process Oriented Guided Inquiry Learning (POGIL) Integrated Flipped Classroom on Problem Solving Ability and Self-Efficacy of High School Students on Thermochemistry Material - Lani Dwi Kurnia; Suyanta (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to determine problem solving ability and self-efficacy simultaneously and respectively of students instructed using Process Oriented Guided Inquiry Learning (POGIL) integrated flipped classroom and the effective contribution. This research is a quasi-experiment with posttest only control group design. The population in this study includes all students of class XI MIPA in senior high school in Mandau Subdistrict. The research samples were taken using cluster random sampling. The research was carried out at SMAN 2 Mandau.  The research instruments are essay questions of problem-solving ability and self-efficacy questionnaires. The data analysis used the MANOVA test with Hotteling's Trace test. The result of the research showed that there are significant differences in problem solving ability and self-efficacy simultaneously and respectively of students instructed using Process Oriented Guided Inquiry Learning (POGIL) integrated flipped classroom with a scientific approach on thermochemistry material and the effective contribution toward problem solving ability and self-efficacy simultaneously on thermochemistry material is 11.50%, problem solving ability 11.30% and self-efficacy 4.80%.